Role of Social Media toward Brand Performance through Mediation of Customer's Satisfaction - Vicentsius Felix Reynaldi; Lena Ellitan; Maria Mia Kristanti (Journal of Entrepreneurship and Business, 2022)
A B S T R A C T This study aims to examine the effect of social media communication, interaction, and motivation toward BBQ Frenzy Brand Performance with the mediating role of customer’s satisfaction and moderating role perceived service quality and trust during COVID-19 Pandemic. To achieve the purpose of the study, the study uses quantitative methods and collecting data in the form of online questionnaire using Google forms from 150 responses of selected group of people which are 18 years old or older, had an Instagram Account, had seen the advertisement about BBQ Frenzy, had visited BBQ Frenzy, and lived in Surabaya, Indonesia during this covid-19 pandemic. The data then analyzed using PLS-SEM in SMART PLS 3.3.3 to test the hypothesis of the study. The result shows that for direct effect social media communication, interaction, and motivation all have a positive and significant effect on the BBQ Frenzy customer’s satisfaction, customer’s satisfaction also shown to have a very strong positive and significant effect on brand performance. As for mediating (indirect) effect it was shown that customer’s satisfaction has a positive and significant effect in mediating social media communication, interaction, and motivation toward BBQ Frenzy brand performance.